Study on Effect of Nozzle Hole Length to Diameter Ratio on Near-Field Diesel Spray Characteristics at High Density Conditions - Dittapoom Shinabuth; Tsuyoshi Nagasawa; Susumu Sato; Hidenori Kosaka (International Journal of Automotive Engineering, 2020)
The diesel engine commonly introduces high boost pressure to achieve high engine efficiency. This extra air is supposed to significantly influence liquid vaporization. In experiment, surrounding gas conditions of 7 – 46.8 kg/m3 were prepared by rapid compression and expansion machine RCEM. The nozzle hole length to diameter L/D ratio of 2.77, 3.73, 4.44 and 6.94 were used corresponding to orifice diameter of 0.072 – 0.180 mm. The close-up region from nozzle tip to 20 mm downstream was focused to simultaneously capture the vapor and liquid phases using shadowgraph and light scattering technique respectively. The information extracted from the images was then used for estimation of fuel mixture in the nearfield spray incorporated with a simple 1D jet model. The result showed that liquid length was dominated by both gas density including gas temperature and rate of fuel injection. The vapor cone angle showed tendency to increase with L/D ratio decreased. The widest vapor cone angle was found at L/D ratio of 2.77 which corresponded to achievement of the highest mass of fuel in vapor phase. It was an evidence that atomization is also one of the essential factors to improve vaporization. At the same gas temperature of 890 K, the fuel mass in liquid phase considerably reduced with increasing gas density. An increase in gas density resulted in substantially increase in entrainment. With identical orifice diameter of 0.180 mm, the smaller L/D=2.77 reported better atomization, shorten liquid length and enhanced entrainment compared with L/D=4.44.